E-mergency: solução mobile para auxílio à regulação do Serviço de Atendimento Móvel de Urgência - SAMU - Barbosa, Luciano de Oliveira (2019)
In this project we approach aspects related to the processes of regulation of urgency and emergency services in the municipality of Campina Grande (PB). These services are operated by users by the unique number 192, intermediated by the Emergency Regulation Center, and performed by the Mobile Emergency Care Service (SAMU), along with accredited hospitals. These, who at the end of the process, will welcome in their bed’s patients affected by acute health problems. In this context, this research aimed to develop a technological solution to improve the communication and synchronization of existing information in this service, assisting the Emergency Regulation Center. The application enables real-time visualization of available beds; the geolocation of ambulances on their travels; recording related information at each occurrence; and the generation of the Digital Prehospital Care Form (FAPH), all in sync with the hospital that will receive the patient, aiming to anticipate the arrival of information. The research was defined as qualitative and applied type, where evaluations were performed with three distinct groups aiming to qualify important aspects of Software Engineering in relation to application development. The final results of these evaluations were considered adequate because, in all evaluations, the average calculations showed a satisfactory value, showing an acceptance greater than 85% in all aspects. The E-mergency application, at the end of the research, proved that with the aid of this technological solution it is possible to achieve a more efficient emergency service.